Penerapan Pembelajaran TGT (Team Games Tournament) pada Materi Sistem Gerak pada Manusia untuk Meningkatkan Motivasi dan Hasil Belajar Siswa - Kurniasih Dwi Wilandari (Academy of Education Journal, 2018)
This research is a type of Classroom Action Research (CAR) which is a research conducted systematically reflective of the actions taken by the teacher as a researcher, ranging from planning, implementing, to assessments to improve learning conditions. In this class action research researchers used two cycles, each of which consisted of four stages: planning, action, observation, and reflection. The research instrument was in the form of a test aimed at finding out student learning outcomes and non-tests in the form of an observation sheet filled out by collaborators, and a student motivation questionnaire sheet filled out by students. The subjects of this study were students of class VIII G of SMP Negeri 1 Nusawungu, totaling 30 students. The data analysis technique used for the assessment process is quantitative descriptive to find out the improvement of student learning outcomes, and qualitative descriptions to determine student motivation.The results of this class action research are the application of the TGT learning model (Team Games Tournament) which provides an increase in student motivation and learning outcomes from pre-cycle, cycle I, cycle II in sequence which has a percentage of graduation of 33.33%; 43.33%; and 83.33%, while the motivation of students from the category is quite good. so it can be concluded that the application of the TGT type of learning model can increase motivation and student learning outcomes.